EVALUATION OF DURABILITY OF LONG-OPERATED POWER PLANT DESIGNS BASED ON THE CALCULATION OF STRESS-STRAIN STATE - Tsybenko, O. S.; Kryshchuk, M. H.; Duravkin, I. P.; Zlakazov, S. O. (Science and Transport Progress, 2006)
There are the considered problems of longevity and durability of elements of power machinecreation in the article.